The Oxidation of 2,4,6-Trinitrotoluene with an Ozone-Oxygen Mixture: A Simple Method for Preparation of 1,3,5-Trinitrobenzene - Mohammad Ali Zarei; Hasan Tahermansouri; Yadollah Bayat (Journal of Chemistry)
The oxidation of 2,4,6-trinitrotoluene (TNT) to 1,3,5-trinitrobenzene (TNB) in one step, 2,4,6-trinitrobenzoic acid (TNBA), and 2,4,6-trinitrobenzaldehyde (TNBAl) with an ozone-oxygen mixture in different solvents, catalysts, and temperatures has been investigated. Reducing the number of steps in the oxidation of TNT to TNB is the major advantage of this procedure with respect to conventional processes such as chromic acid and potassium permanganate. The oxidation of TNT to TNB was completed in one step as compared to two steps in the conventional approach. The products were obtained with relatively good yield.